Appropriate Frequency and Interval of Neck Ultrasonography Surveillance during the First 10 Years after Total Thyroidectomy in Patients with Papillary Thyroid Carcinoma - Lee, Yoo Jin; Kim, Dong Wook; Shin, Gi Won; Heo, Young Jin; Baek, Jin Wook; Cho, Young Jun; Park, Young Mi; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Park, Ji Sun; et al. (Frontiers in Endocrinology, 2018)
Background: No previous study has employed the frequency and interval of follow-up ultrasonography (US) during the first 10 years after total thyroidectomy in patients with papillary thyroid carcinoma (PTC). The aim of this study was to determine the appropriate frequency and interval of follow-up US during the first 10 years in patients who have undergone total thyroidectomy for PTC. Methods: Two hundred and seventy-two patients underwent total thyroidectomy for PTC at our institution from January 2006 to December 2007. Nineteen patients were excluded because of lack of US follow-up data for the neck. Follow-up US was performed by one of two radiologists in all patients. Tumor recurrence/persistence was confirmed by histopathology. Results: The mean interval between surgery and the final follow-up US examination was 79.0 months and the mean number of follow-up US sessions was 5.9 in the 253 evaluable patients. Eleven patients (4.3%) developed tumor recurrence/persistence, which was detected on follow-up US within 5 years after total thyroidectomy in all cases. T and N stages were independently associated with tumor recurrence/persistence. The interval between surgery and first suspicion of tumor recurrence/persistence on follow-up US was ≤12 months in 6 patients and 20, 35, 41, 53, and 60 months in the remaining 5 patients. Conclusions: For detection of tumor recurrence/persistence after total thyroidectomy in patients with PTC, 1 or 2 sessions of follow-up US during the first 2 years, depending on T and N stages and 1 session of follow-up US every second year during the following 8 years may be appropriate.